Comparison of curved canals preparations using profile, GT and Hero 642 rotary files - (:unkn) unknown (BLACKWELL PUBLISHING, 2006)
This study compared preparations of curved canals, using Profile, GT file and Hero 642 rotary files. A total of 30 mesiobuccal canals of extracted first and second mandibular molars were used in this study. The teeth were embedded in resin and a pre-operative radiograph was taken. The specimens were then randomly divided into three instrument groups. Pre- and post-instrumentation radiographic images were scanned and superimposed using the visi cad/cam program. At nine horizontal sections at 1 mm increments from the apex, it calculated pre- and post-instrumentation cross sectional areas (mm(2)) and enlargements to the inner aspect and outer aspects (mm). A Kruskal-Wallis test found no statistical difference among the groups in terms of total areas removed by each instrument (P > 0.05). It also found no significant difference in any group between the total of the inner and outer enlargements (P > 0.05). However the GT file removed significantly more material from the outer side of the canal than the inside at sections 3-5, and the Hero removed significantly more material from the outer side at sections 7-9 (P < 0.05). All instruments produced preparations that maintained original canal curvatures.
Keywords: nickel-titanium; root canal preparation; rotary files; NICKEL-TITANIUM INSTRUMENTS; SIMULATED ROOT-CANALS; SHAPING ABILITY; PART 2; ENDODONTIC INSTRUMENTS; ENGINE